Experimental and Numerical Investigation of Fracture Behavior of Particle-Reinforced Alkali-Activated Slag Mortars - Nayak, Sumeru; Kizilkanat, Ahmet; Neithalath, Narayanan; Das, Sumanta (ASCE-AMER SOC CIVIL ENGINEERS, 2019)
This paper presents fracture responses of alkali-activated slag (AAS) mortars with up to 30% (by volume) of slag being replaced by waste iron powder that contains a significant fraction of elongated iron particles. The elongated particles act as microreinforcement and improve the crack resistance of AAS mortars by enlarging the fracture process zone (FPZ). An enlarged FPZ signifies increased energy dissipation, which is reflected in a significant increase in crack growth resistance as determined from R-curves. Fracture responses of notched AAS mortar beams under three-point bending are simulated using the extended finite-element method (XFEM) to develop a tool for direct determination of fracture characteristics such as crack extension and fracture toughness in particulate-reinforced AAS mortars. Fracture response simulated using the XFEM framework correlates well with experimental observations. The comprehensive fracture studies reported here provide an economical and sustainable means of improving the ductility of AAS systems, which are generally more brittle than their conventional portland cement counterparts.
Keywords: Alkali-activated slag; Particulate reinforcement; Fracture response; Digital image correlation; Extended finite-element method; DRYING SHRINKAGE; CRACK-GROWTH; PROCESS ZONE; FLY-ASH; CONCRETE; STRENGTH; BINDERS; TENSILE; MODEL; DISPLACEMENT; Construction & Building Technology; Engineering; Materials Science